Evaluation of Losses and Life of Distribution Transformer under Non-linear Load using Wavelet Transfor: Wavelet Based Analysis of Transformer Loss & Life - Hassan, Rizwan Ul; Shami, Umar Tabrez; Safdar, Adnan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this paper, impact of harmonics on losses and life of distribution transformer is discussed. Wavelet Transform is used to analyze voltage and current signatures of distribution transformer operating under non-linear load. Power loss is calculated using wavelet based current and voltage profiles. Reduction in life time of the transformer has also been calculated which results due to harmonics in power system. Results show that power loss of a transformer increases under non-linear load as compared to its usage under linear loading, increase in power loss causes decay in transformer’s operational life.